ANALYZING HOMOGRAPHS IN ACEHNESE AND ENGLISH LANGUAGES - Tursina, Puan; Rahmatan, Eka (STKIP Bina Bangsa Getsempena Banda Aceh, 2017)
The aims of this study were to figure out the number of homographs in Acehnese and English languages and the examples of homographs. Qualitative approach was used to conduct the study. Both Acehnese dictionary and Oxford dictionary were used to collect the data. The results of the study indicated that there were 157 words found between Acehnese and English languages. In addition, those words were written in the same spelling but those are different from the meanings and pronunciation. It was clear that interlingual homograph can be found between Acehnese and English words.Keywords: Language, Acehnese, English, Homograph